2018
DOI: 10.1002/14651858.cd006112.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle training for cystic fibrosis

Abstract: Analysis 3.4. Comparison 3 RMT (40% of maximal e ort) versus control, Outcome 4 Forced vital capacity (% predicted)............ Analysis 3.5. Comparison 3 RMT (40% of maximal e ort) versus control, Outcome 5 Inspiratory muscle endurance (% PImax)..... Analysis 4.1. Comparison 4 RMT (20% of maximal e ort) versus control, Outcome 1 Forced expiratory volume at one second

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…In addition, respiratory exercises, such as respiratory muscle training and chest physiotherapy, have short-term effects in terms of increasing mucus transport and airway clearance. 9,10 Although both general and respiratory exercises are recommended by clinical guidelines of CF, 11 nonadherence to prescribed interventions is common in chronic diseases. 12 Multiple therapies with an exhaustive treatment routine, in addition to the lack of curative treatment, 13 may be an aggravating factor to non-adherence to exercises in CF, which is associated with increased risk of hospitalization, longer hospital stays, and pulmonary exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, respiratory exercises, such as respiratory muscle training and chest physiotherapy, have short-term effects in terms of increasing mucus transport and airway clearance. 9,10 Although both general and respiratory exercises are recommended by clinical guidelines of CF, 11 nonadherence to prescribed interventions is common in chronic diseases. 12 Multiple therapies with an exhaustive treatment routine, in addition to the lack of curative treatment, 13 may be an aggravating factor to non-adherence to exercises in CF, which is associated with increased risk of hospitalization, longer hospital stays, and pulmonary exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…These two adaptations jointly facilitate the ability to walk at a certain intensity for a long time without decreasing the SpO 2 . On the other hand, it is also known that IMT improves the strength of the inspiratory musculature, allowing lung pathology patients to overcome and "train" pulmonary compliance [35,37]. This allows patients to maintain a larger alveolar gas exchange surface, as there is a better expansion of lungs, and to maintain a higher VE at a high intensity of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent limited utility of IMT to translate to clinically meaningful outcomes must be interpreted in the context of multiple methodological limitations and the obvious paucity of available studies. Indeed, the most recent Cochrane review only identified nine reports eligible for inclusion [20]. Whilst the overall conclusion of this review appears to be appropriate based on the available evidence, several parameters that may underpin the equivocal findings were not adequately discussed, such as the methods utilized to quantify respiratory muscle function [36].…”
Section: Current State Of Imt In Cfmentioning
confidence: 99%
“…Strategies to enhance respiratory muscle function in the presence of a load/capacity imbalance and to counteract the disease-related decline in pulmonary function have been suggested, with one potential strategy being IMT [20, 21]. While specific loading protocols vary, IMT typically utilizes either a pressure or volume load on the inspiratory muscles to provide a stimulus to elicit a training response [22], similar to that observed in response to training peripheral musculature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation